The Heterogeneity of Family Firms in CSR Engagement: The Role of Values. (September 2014) - Marques, Pilar; Presas, Pilar; Simon, Alexandra
This study addresses the heterogeneity of family firms in their engagement with corporate social responsibility (CSR). We build on stewardship theory and socioemotional wealth to explore the foundations of CSR in family firms and to examine whether the extent of engagement is based on values, and how and why this happens. We use the interpretative method of grounded theory to address these questions. Based on 12 case studies of Spanish family firms, this article illustrates the patterns of influence of family involvement and values in explaining the extent and scope of CSR.